2018
DOI: 10.1074/jbc.m117.809889
|View full text |Cite
|
Sign up to set email alerts
|

The telomerase inhibitor AZT enhances differentiation and prevents overgrowth of human pluripotent stem cell–derived neural progenitors

Abstract: Human pluripotent stem cell (hPSC)-based cell-replacement therapy has emerged as a promising approach for addressing numerous neurological diseases. However, hPSC transplantation has the potential to cause human cell overgrowth and cancer, which represents a major obstacle to implementing hPSC-based therapies. Inhibition of the overgrowth of transplanted cells could help reduce the risk for hPSC transplantation-induced tumorigenesis. In this study, we report that the telomerase inhibitor azidothymidine (3'-azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…The augmented recovery of EdU+ cells from young brains facilitated the identification of rare proliferating cell types previously overlooked, such as arachnoid barrier cells located within the blood- cerebrospinal fluid (CSF) barrier 64 and pituitary stem cells from the pituitary gland 65 ( Figure S5 ). Notably, the telomerase inhibitor resulted in enriched intermediate neuroblasts, associated with reduced fraction of early progenitor cells and late-stage differentiated cells along the neurogenesis trajectory ( Figures S4K and S4L ), consistent with previous studies 54 , 66 , 67 ( Figure S4M ). This analysis demonstrates the potential of TrackerSci to aid in characterizing cell proliferation and differentiation dynamics upon in vivo perturbations.…”
Section: Resultssupporting
confidence: 91%
“…The augmented recovery of EdU+ cells from young brains facilitated the identification of rare proliferating cell types previously overlooked, such as arachnoid barrier cells located within the blood- cerebrospinal fluid (CSF) barrier 64 and pituitary stem cells from the pituitary gland 65 ( Figure S5 ). Notably, the telomerase inhibitor resulted in enriched intermediate neuroblasts, associated with reduced fraction of early progenitor cells and late-stage differentiated cells along the neurogenesis trajectory ( Figures S4K and S4L ), consistent with previous studies 54 , 66 , 67 ( Figure S4M ). This analysis demonstrates the potential of TrackerSci to aid in characterizing cell proliferation and differentiation dynamics upon in vivo perturbations.…”
Section: Resultssupporting
confidence: 91%
“…Next, MCF-7 cells were preincubated with TE inhibitor AZT with different concentrations for 24 h, respectively, and then incubated with TPP-Y and TAMRA-labeled and BHQ2-modified T-L-DNA (denoted as TPP-Y-T-L) for 12 h. The images of CLSM showed that the fluorescence in the MCF-7 cells gradually decreased as the AZT concentration increased (Figure S14). This result revealed that the disassembly of T-L-DNA depended on the TE activity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To that end, future studies will look into alternative media specifically designed for primary cell cultures. Early literature has found that BrainPhys neuronal media from StemCell Technologies promotes synaptic activity, neuron differentiation, and cell health of primary human stem cells over the long term, with cultures lasting up to 18 weeks 179,180 . Further, the criteria used for cell selection may be biasing for cells at certain developmental stages.…”
Section: Discussionmentioning
confidence: 99%